Evaluation Of The Implications Of Coretax Use Based On User Perceptions - Deviana Deviana; Dwi Martani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Directorate The General Directorate of Taxes (DGT) launched system CoreTax as part from digital transformation of taxation For simplify administration and improve efficiency service tax system​ This start implemented on January 1, 2025, but at the stage beginning its implementation Still found various constraints . Therefore that , research This conducted in the period of October 2025 for evaluate whether problem beginning the Still continued . Research This aim evaluate perception must tax to CoreTax use Technology Acceptance Model (TAM) approach as well analyze its relevance with efficiency and compliance taxation . The research method used is qualitative descriptive with primary data collection through questionnaires and interviews , as well as secondary data from document official and research previous research results show that based on perception users , CoreTax assessed capable increase efficiency and compliance taxation through convenience usage , data validation , and integration system . However , until October 2025, the problems faced users Still relatively the same , so that optimization and refinement system still required For increase quality service and experience user.